2017
DOI: 10.1159/000451027
|View full text |Cite
|
Sign up to set email alerts
|

Rutin Attenuates Oxidative Stress and Proinflammatory Cytokine Level in Adjuvant Induced Rheumatoid Arthritis via Inhibition of NF-κB

Abstract: The present study was intended to elucidate the effect of rutin, a flavonoid, on arthritis in complete Freund's adjuvant-induced arthritic rats. The present study showed that more pronounced effect has been observed in the case of 15 mg/kg dose of rutin, with significant reduction in paw diameter together with positive modulation of hematological parameters as compared to 2 other tested doses. A significant upsurge in the level of superoxide dismutase, glutathione peroxidase and glutathione were observed toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Among them, p50 and p65 are the most relevant subunits to RA synoviocytes by immunohistochemistry [ 5 ]. Prior studies showed that suppression of NF-κB p65, the main effector subunit of the classical NF-κB pathway, protects against RA [ 36 ]. The transcriptional activity of p65 could be further regulated by phosphorylation and acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, p50 and p65 are the most relevant subunits to RA synoviocytes by immunohistochemistry [ 5 ]. Prior studies showed that suppression of NF-κB p65, the main effector subunit of the classical NF-κB pathway, protects against RA [ 36 ]. The transcriptional activity of p65 could be further regulated by phosphorylation and acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, histopathological examination showed that the inflammatory cells infiltration, synovial hyperplasia, pannus formation and cartilage and bone erosion had considerably improved on administration of rutin. Thus, these findings demonstrated the protective effect of rutin against rheumatoid arthritis via suppression of NF-κB p65 protein expression (Sun et al, 2017).…”
Section: Antiarthritis Propertymentioning
confidence: 64%
“…Our investigations also explored that CFA-induced arthritis elevated MDA, and reduced GSH contents in the articular tissue. Similarly, different studies have demonstrated oxidant/antioxidant imbalance after CFA-induced arthritis ( Liu et al, 2017 , Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%